Pricing of European Currency Options with Uncertain Exchange Rate and Stochastic Interest Rates - Xiao Wang (Discrete Dynamics in Nature and Society)
Suppose that the interest rates obey stochastic differential equations, while the exchange rate follows an uncertain differential equation; this paper proposes a new currency model. Under the proposed currency model, the pricing formula of European currency options is then derived. Some numerical examples recorded illustrate the quality of pricing formulas. Meanwhile, this paper analyzes the relationship between the pricing formula and some parameters.